Caudal Regression Syndrome: A Rare Case Report - Sharmin, Lazina; Akter, Shaheen; Hossain, Md Ismail; Musa, Abu Saleh (Bangladesh Journal of Child Health, 2018)
Caudal regression syndrome is a rare disorder characterized by abnormal development of structures in the caudal region of the embryo like lower lumbar and sacral vertebrae, urogenital and lower gastrointestinal system occur in early gestation. It’s a sporadic disorder. Maternal diabetes, genetic predisposition and vascular hypo perfusion have been shown to be associated with its pathogenesis. Here we report a newborn of diabetic mother diagnosed as caudal regression syndrome type II. Treatment for this patient is multidisciplinary. So, after giving necessary supportive treatment we discharged the patient with proper advice of his further management to improve the prognosis. Bangladesh J Child Health 2018; VOL 42 (3) :159-161